Adolescent menorrhagia - Skrzypulec-Plinta, Violetta; Drosdzol-Cop, Agnieszka (Menopause Review/Przegląd Menopauzalny, 2010)
Adolescent menorrhagia is defined as uterine bleeding lasting more than 10 days and/or severe uterine bleeding with a total menstrual blood loss of more than 80ml, causing anaemia. Such uterine bleeding episodes might occur up to 5 years after menarche; are characterized by differential time of abnormal bleeding and its severity: from moderate to heavy menstruation. This is the common form of irregular menstruation in adolescent females and is usually functional. The pathophysiology of adolescent menorrhagia is: lack of ovulation with a low oestrogen level, luteal phase insufficiency or disturbances of myometrium and vascular contractibility. Adolescent menorrhagia may present as mild, moderate or heavy bleeding